2006
DOI: 10.1002/pola.21590
|View full text |Cite
|
Sign up to set email alerts
|

First synthesis of the bismole‐containing conjugated polymer

Abstract: We successfully synthesized the first conjugated polymer containing a bismuth atom in the conjugated main chain by incorporating a bismuth atom into the cyclopentadiene framework (bismole), which was constructed by a polymer reaction. A synthetic procedure and characterization of the obtained polymers were discussed. This bismole‐containing conjugated polymer exhibited moderate bluish green photoluminescence in solution. © 2006 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 44: 4857–4863, 2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
(51 reference statements)
0
16
0
2
Order By: Relevance
“…[176] Metallapolymer precursor approaches have also been used to incorporate phospholes,a rsoles,a nd bismoles into polymers.T omita, Naka et al's. [178] [177] In addition, Chujo et al demonstrated that iodination of az irconacycle-containing polymer followed by alithium-iodine exchange and treatment with PhBiBr 2 generates the respective bismole polymer.…”
Section: Reviewsmentioning
confidence: 99%
“…[176] Metallapolymer precursor approaches have also been used to incorporate phospholes,a rsoles,a nd bismoles into polymers.T omita, Naka et al's. [178] [177] In addition, Chujo et al demonstrated that iodination of az irconacycle-containing polymer followed by alithium-iodine exchange and treatment with PhBiBr 2 generates the respective bismole polymer.…”
Section: Reviewsmentioning
confidence: 99%
“…Die Beständigkeit gegen oxidativen Abbau ist wichtig fürAnwendungen in der Optoelektronik. [178] 4.4. [176] Metallapolymer-Vorstufen wurden auch verwendet, um Phosphole,Arsole und Bismole in Polymere einzufügen.…”
Section: Angewandte Chemieunclassified
“…Eine elegante Synthese von orange lumineszierenden Arsol-Polymeren 102 ausgehend von Titanacyclen nach Tomita, Naka et al ist in Schema 11 (unten) veranschaulicht [177]. Darüber hinaus zeigten Chujo et al,d ass die Iodierung eines Zirconacyclus-haltigen Polymers,g efolgt von einem Lithium-Iod-Austausch und der Umsetzung mit PhBiBr 2 ,das jeweilige Bismol-Polymer bildet [178]. 4.4.…”
unclassified
“…However, investigations of “arsoles” from the viewpoint of materials science remain to be performed, although some arsole derivatives were synthesized up to the 1960s . If studies on pnictogen‐type heteroles are performed by experimental means, pyrrole, phosphole, stibole, and bismole derivatives are prepared, but their arsenic analogues tend to be excluded. Nevertheless, computational studies have constantly predicted the intrinsic natures of arsoles: frontier orbitals, inversion energies, and aromaticity .…”
Section: Introductionmentioning
confidence: 99%
“…However,i nvestigations of "arsoles" from the viewpoint of materials science remaint ob ep erformed, although some arsole derivatives were synthesized up to the 1960s. [4][5][6][7][8] If studies on pnictogen-type heteroles are performed by experimental means, pyrrole, [9][10][11][12][13] phosphole, [14][15][16][17] stibole, [18,19] and bismole [20][21][22] derivatives are prepared, but their arsenic analoguest end to be excluded.N evertheless, computational studies have constantly predicted the intrinsic natures of arsoles: frontier orbitals, inversion energies, and aromaticity. [23][24][25][26][27][28][29][30] Ta king into consideration growingi nterest in heavy-element-containing molecules, [31] studies on functional organoarsenic chemistry is attractive thanks to the air-stable trivalent state [3] and possibility of the heavy-atom effect.…”
Section: Introductionmentioning
confidence: 99%